2013
DOI: 10.1007/s10936-013-9277-z
|View full text |Cite
|
Sign up to set email alerts
|

A Normative Database and Determinants of Lexical Retrieval for 186 Arabic Nouns: Effects of Psycholinguistic and Morpho-Syntactic Variables on Naming Latency

Abstract: Research into lexical retrieval requires pictorial stimuli standardised for key psycholinguistic variables. Such databases exist in a number of languages but not in Arabic. In addition there are few studies of the effects of psycholinguistic and morpho-syntactic variables on Arabic lexical retrieval. The current study identified a set of culturally and linguistically appropriate concept labels, and corresponding photographic representations for Levantine Arabic. The set included masculine and feminine nouns, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 39 publications
0
27
0
Order By: Relevance
“…Akinina, Malyutina, Ivanova, Iskra, Mannova, Dragoy, 2014;Bonin, Mèot, Chalard, & Fayol, 2002;Bonin, Peereman, Malardier, Mèot, & Chalard, 2003; Cameirao & Vicente 2010). Khwaileh et al (2014;2018) reported that this variable is a significant predictor of successful lexical retrieval in Levantine Arabic and Gulf Arabic.…”
Section: Factors Influencing Word Processingmentioning
confidence: 99%
See 3 more Smart Citations
“…Akinina, Malyutina, Ivanova, Iskra, Mannova, Dragoy, 2014;Bonin, Mèot, Chalard, & Fayol, 2002;Bonin, Peereman, Malardier, Mèot, & Chalard, 2003; Cameirao & Vicente 2010). Khwaileh et al (2014;2018) reported that this variable is a significant predictor of successful lexical retrieval in Levantine Arabic and Gulf Arabic.…”
Section: Factors Influencing Word Processingmentioning
confidence: 99%
“…According to Khwaileh et al (2014;2018), 'word frequency' is defined as "how frequent a word is used (spoken or written form) in a given language". The assumption is that the higher the frequency of a given word, the faster the processing and the more accurate the response in picture naming (Martein,1995;Nickels, 1997).…”
Section: Factors Influencing Word Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…Norms have recently been established for Levantine Arabic, one of the DA varieties spoken in the Middle East (Khwaileh, Body, & Herbert, 2014). However, the ratings were collected for a different and smaller set (n = 186 pictures) than the commonly used Snodgrass and Vanderwart (1980) pictorial database (e.g., Alario & Ferrand, 1999;Cycowicz et al, 1997;Dimitropoulou et al, 2009;Manoiloff et al, 2010;Nisi et al, 2000;Raman et al, 2014;Sanfeliu & Fernandez, 1996;Tsaparina, Bonin, & Méot, 2011).…”
mentioning
confidence: 99%